2005
DOI: 10.1158/1078-0432.ccr-05-0632
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Cytoskeletal Protein Composition Indicative of an Epithelial-Mesenchymal Transition in Human Micrometastatic and Primary Breast Carcinoma Cells

Abstract: Purpose:The bone marrow is a frequent and clinically important homing site for early disseminated breast cancer cells. Here, we aimed to profile the protein expression of these cells using unique cell line models and to evaluate the prognostic relevance of candidate gene expression for breast cancer patients. Experimental Design: To identify expression patterns characteristic for micrometastatic cells, three different cell lines (BC-K1, BC-P1, and BC-S1) established by SV40 immortalization of cancer cells isol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
215
1
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 280 publications
(231 citation statements)
references
References 35 publications
12
215
1
1
Order By: Relevance
“…During tumor growth and progression, the local microenvironment and growth factors may induce epithelial tumor cells to dedifferentiate and acquire an epithelial mesenchymal transition like phenotype characterized by loss of cell to cell adhesion, down regulation of E-cadherin and a shift of intermediate filaments to vimentin [25]. Suppression of CK19 expression in carcinomas during tumor differentiation has been reported in both human tissues, such as breast cancers, and cultured malignant cell lines [26,27]. Down-regulation of CK19 expression and overexpression of vimentin were found in highly aggressive breast cancer cells with strong migratory and invasive abilities [28].…”
Section: Discussionmentioning
confidence: 99%
“…During tumor growth and progression, the local microenvironment and growth factors may induce epithelial tumor cells to dedifferentiate and acquire an epithelial mesenchymal transition like phenotype characterized by loss of cell to cell adhesion, down regulation of E-cadherin and a shift of intermediate filaments to vimentin [25]. Suppression of CK19 expression in carcinomas during tumor differentiation has been reported in both human tissues, such as breast cancers, and cultured malignant cell lines [26,27]. Down-regulation of CK19 expression and overexpression of vimentin were found in highly aggressive breast cancer cells with strong migratory and invasive abilities [28].…”
Section: Discussionmentioning
confidence: 99%
“…For example, in breast epithelia, K8 and K18 are expressed in the differentiated compartment and are down-regulated in a high percentage of breast carcinomas, a feature that correlates with a worse prognosis (13,26,27). Similarly, micrometastatic cell lines derived from the bone marrow of breast cancer patients showed loss of cytokeratin expression with concomitant up-regulation of vimentin (28). Furthermore, these authors were able to correlate changes in keratin and vimentin expression with more aggressive lesions, indicating clinical significance.…”
Section: Discussionmentioning
confidence: 99%
“…It has long been recognized that CTCs show reduced expression of specific cytokeratins (Pantel et al, 1994). More recently, Pantel and coworkers have shown that cell lines derived from breast cancer micrometastases stably express the mesenchymal marker vimentin (Willipinski-Stapelfeldt et al, 2005). The possible roles of EMT in escape and survival in the blood stream as CTCs, and establishment as micrometastases, are summarized in Figure 3.…”
Section: Clinical and Translational Perspectivesmentioning
confidence: 99%